From quantum to cosmos : fundamental physics research in space - Turyshev, Slava G. (World Scientific, 2009)
Space-based laboratory research in fundamental physics is an emerging research discipline that offers great discovery potential and at the same time could drive the development of technological advances which are likely to be important to scientists and technologists in many other different research fields. The articles in this review volume have been contributed by participants of the international workshop "From Quantum to Cosmos : Fundamental Physics Research in Space" held at the Airlie Center in Warrenton, Virginia, USA, on May 21-24, 2006. This unique volume discusses the advances in our understanding of fundamental physics that are anticipated in the near future, and evaluates the discovery potential of a number of recently proposed space-based gravitational experiments. Specific research areas covered include various tests of general relativity and alternative theories, search of physics beyond the Standard Model, investigations of possible violations of the equivalence principle, search for new hypothetical long- and short-range forces, variations of fundamental constants, tests of Lorentz invariance and attempts at unification of the fundamental interactions. The book also encompasses experiments aimed at the discovery of novel phenomena, including dark matter candidates, and studies of dark energy.